Strategi IMC (Integrated Marketing Communication) Sebagai Survivor Bisnis Online Di Masa dan Pasca Pandemi - Musrifah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
The prolonged Covid-19 pandemic brought many changes to the dynamics of the national economy. One of them is the proliferation of online business among the public. In the midst of the community's economic crisis due to the pandemic and its consequences, online businesses are increasingly showing their existence as economic heroes who are proven to survive in the midst of a crisis. This article attempts to disassemble the strategies that online businesses can do by using the principles of IMC (Integrated Marketing Communication) which have been known for a long time in the marketing world and have been proven in many researches. However, IMC has not been popularly known or even applied in online business. Several elements of IMC that can increase turnover and survive online businesses during and after the pandemic are: Advertising, Personal Selling, Direct Marketing, and Public Relations. Behind these elements there are still other strategies that can be applied in today's online business.